Changing Paths and Surviving as an Entrepreneur: Psychological Resilience in Layoff Victims - Syaiful Fakhri (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2023)
The Covid-19 pandemic that has passed has brought about changes in the economic life of the community, including in livelihoods. Not a few people had to change professions due to layoffs from their companies during the pandemic, and now they are turning into entrepreneurs or opening businesses to meet their daily needs. This study aims to provide an overview of the dynamics of psychological resilience in business actors affected by layoffs from the co-19 pandemic with a qualitative phenomenological approach. Informants in this study involved 2 people who are entrepreneurs. The informant criteria are workers who have been affected by layoffs during the pandemic, have a business, and are currently not returning to formal employment. The data collection methods used were interviews and observations. The results showed that psychological resilience in the two informants was described by Tenacity, Strength, and Optimism. Tenacity can be seen from the determination to run a business after being laid off, believing that fortune has been arranged by God and the informant's gratitude brings a path to entrepreneurship. Strenght is seen from the attitude of willingness to sacrifice, a strong intention to run, and from the family who helped strengthen what the informant is currently living. Optimism in informants, namely informants believe in what is currently being lived as a life choice, and persistence to see the prospects of the business being undertaken for their future lives.Keywords: Entrepreneur, Layoff Victims, Resilience.